Development of Project-Based Learning Models for Teaching Accounting English in Higher Education - Marina Marina; Mursidah Mursidah; Muhammad Roni (English Teaching and Linguistics Journal (ETLiJ), 2022)
This study examines the development of project-based learning model for teaching English for Spesific Purpose (ESP) in Accounting Study Program at the Faculty of Economics and Business, Malikussaleh University. The first stage of data was obtained by conducting interviews with lecturers to obtain preliminary data. Interviews were conducted with lecturers in English courses and lecturers in the Accounting study program to get an idea of the appropriate project material. The second stage is the development of a project-based learning model prototype based on the results of interviews. Furthermore, this prototype was validated by two validators, namely material experts and evaluation and assessment experts. The model was revised based on feedback from the validator to create a project-based learning model that was ready to be implemented. The results of this study create a project-based learning model that can be applied by lecturers in teaching English for accounting in higher education.